Kondisi Sanitasi Pada Kapal Kargo Di Wilayah Kerja Kantor Kesehatan Pelabuhan (KKP) Kelas III Manokwari - Syamsudin Syamsudin; Vera Sabariah; Meike M. Lisangan; Zita L Sarungallo; Hendri Hendri; Yuanike Kaber (Cassowary, 2021)
Ship sanitation and its environment are a mandate from International Health Regulation (IHR)2005 and the regulation of Ministry of Health Republic IndonesiaNo 40 Tahun 2015 that request all the ship in Indonesia territory should have a certificate of ship sanitation. This is due to prevent, protect and control spreading of diseases. This study aimed to analyze the sanitation condition of cargo ships in working area of Harbour Health Office (KKP) type III Manokwari. Research location was done in Manokwari Harbour on September to October 2020. Method used in this study was descriptive approach and direct observation. Sample was obtained by purposive sampling, that 13 (thirteen) cargo ships anchored in Manokwari. Variables observed included room sanitation, vector, foods and drinking water, and waste. Results showed that in general the sanitation of the 13 cargo ships was qualified good (91.21%), except for warehouse and medical facilitation. There were two ships (15.38%) unqualified because had no storage room for dry and wet foods. Moreover, six cargo ships (46.15%) had no medical facilitation according to the requirement, but only some medicines without observation room and medical tools. On the other hands, the vector and disease-spread animals, management food and drinking water, as well as the waste management for 13 cargo ships were qualified.